Theosis in Luther: Analysis of the New Finnish Luther Research - Lytvynenko, Viacheslav (Bogoslovskie razmyšlenija, 2013)
The article is focused on the new Finnish Luther research that attempts to establish a point of contact between Lutheran and Orthodox traditions by claiming that Luther’s idea of Christ’s indwelling corresponds to the Orthodox doctrine of theosis (also known as deification, or participation in God). In opposition to the traditional forensic understanding of justification, Finnish scholars reinterpret the motif of Christ’s presence in Luther and affirm that he understood salvation interms of participation in God along the lines of patristic soteriology. While the research is grounded on the intention of finding common points of dialogue between the two theological traditions, it can be argued that Finnish perspective can be improved by revising its essentialist description of participation in God inlight of the Orthodox essenceenergies distinction.